Switching and its Impact on Perseveration in a Verbal Fluency Task: a Study in Persons With Alzheimer’s Clinical Syndrome - Dubey, Neha; Basu, Jayanti; Pandey, Dinkar; Ghosh, Amitabha (Archives of clinical neuropsychology, 2025)
The relationship between perseveration and switching in semantic verbal fluency tasks and the possible role of self-generated interference one must overcome before switching back to a previously visited subcategory has not been explored. We studied the performance on semantic verbal fluency in 60 cognitively unimpaired subjects, 30 patients with amnestic mild cognitive impairment (aMCI) and 30 patients with Alzheimer's Clinical Syndrome-dementia (ACS-Dementia). Our primary analysis focused on the association of switching and switchback with the first perseverative error. Perseveration was significantly associated with switchback in all three groups (χ2 = 24.88, p < .001). Within-cluster perseverations were few. The number of switchbacks was the only significant variable to predict perseverative responses (p < .01). Moving from cognitively unimpaired to aMCI to ACS-Dementia, progressively fewer switches and switchbacks were needed to trigger perseveration. In over half of the perseverations after a switchback in the cognitively unimpaired and aMCI groups and in over a third in the ACS-Dementia group, the subjects had already activated a new word in the switched back subcategory. Switching between subcategories and subsequent switchback play an important role in triggering perseverations in semantic verbal fluency tasks in the cognitively unimpaired as well as in aMCI and ACS-Dementia. Self-generated interference caused by repeated switching may overwhelm the working memory capacity enough to reactivate a previously suppressed response when revisiting an earlier subcategory. Our findings may facilitate a deeper understanding of the cognitive mechanisms underlying perseveration in semantic fluency tests.